UV Light-Induced Response Degradation Characteristics of Silicon-Based Detectors - Daniel Gäbler; Pablo F. Siles (Proceedings)
High energy radiation is known to potentially impact silicon-based optical sensors adversely, either permanently or reversibly [...]